2017
DOI: 10.1097/wnn.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

Predictors That a Diagnosis of Mild Cognitive Impairment Will Remain Stable 3 Years Later

Abstract: Background and Objective In half to two thirds of patients who are diagnosed with mild cognitive impairment (MCI), the diagnosis neither converts to dementia nor reverts to normal cognition; however, little is known about predictors of MCI stability. Our study aimed to identify those predictors. Methods We obtained 3-year longitudinal data from the National Alzheimer’s Coordinating Center Uniform Data Set for patients with a baseline diagnosis of MCI. To predict MCI stability, we used the patients’ baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…A prospective population-based study in the elderly showed that the conversion rate of MCIc patients to AD or to different forms of dementia is about 10-15% per year (Mitchell and Shiri-Feshki, 2009;Lopez et al, 2012;Wei et al, 2016). Despite our substantial knowledge of MCI converters, little is understood about the 47-67% (Ganguli et al, 2004;Lopez et al, 2012;Clem et al, 2017) of subjects diagnosed with MCI who neither return to normal cognition nor convert to dementia. In a study performed in a large community sample, 10 years identified as a MCI, 21% of those suspected to be at a greater risk for converting to dementia (Dubois and Albert, 2004;Jicha et al, 2006) managed to remain with a diagnosis of MCI (Ganguli et al, 2004;Clem et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective population-based study in the elderly showed that the conversion rate of MCIc patients to AD or to different forms of dementia is about 10-15% per year (Mitchell and Shiri-Feshki, 2009;Lopez et al, 2012;Wei et al, 2016). Despite our substantial knowledge of MCI converters, little is understood about the 47-67% (Ganguli et al, 2004;Lopez et al, 2012;Clem et al, 2017) of subjects diagnosed with MCI who neither return to normal cognition nor convert to dementia. In a study performed in a large community sample, 10 years identified as a MCI, 21% of those suspected to be at a greater risk for converting to dementia (Dubois and Albert, 2004;Jicha et al, 2006) managed to remain with a diagnosis of MCI (Ganguli et al, 2004;Clem et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite our substantial knowledge of MCI converters, little is understood about the 47-67% (Ganguli et al, 2004;Lopez et al, 2012;Clem et al, 2017) of subjects diagnosed with MCI who neither return to normal cognition nor convert to dementia. In a study performed in a large community sample, 10 years identified as a MCI, 21% of those suspected to be at a greater risk for converting to dementia (Dubois and Albert, 2004;Jicha et al, 2006) managed to remain with a diagnosis of MCI (Ganguli et al, 2004;Clem et al, 2017). These studies suggest that certain subjects may not convert to AD, but rather remain diagnostically stable over a period of time (this type of patient falls into an MCI-stable, or MCIs group).…”
Section: Introductionmentioning
confidence: 99%
“…Predictors of stability include better neuropsychological test results (especially in speed of mentation and memory recall), younger age at diagnosis, and an absence of ApoE4. 23 Patients belonging to this category either had a single-phase damage to the brain or, more likely, have staved off progression to dementia via cognitive reserve or other less well understood mechanisms. 3.…”
Section: Mild Cognitive Impairment As a Prodromal Stage Of Neurodegenmentioning
confidence: 99%
“…In a 2-year follow-up study of patients with MCI, it was found that multiple domains MCI, with or without memory impairment included, had even higher sensitivity than amnestic MCI alone in identifying subjects at risk of developing AD or vascular dementia, while amnestic MCI had higher specificity 56. Having a higher baseline scores on delayed recall, processing speed and global function; younger age and absence of apolipoprotein E4 alleles, were more likely associated with stable MCI 57. As to biomarkers, there is insufficient evidence to recommend their use in predicting progression of cognitive impairment 58…”
Section: Definitions and Diagnostic Criteriamentioning
confidence: 99%